2018
DOI: 10.1021/acs.nanolett.8b00809
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Nanocrystals in Spherical Confinement Probed by in Situ X-ray Scattering

Abstract: We studied the formation of supraparticles from nanocrystals confined in slowly evaporating oil droplets in an oil-in-water emulsion. The nanocrystals consist of an FeO core, a CoFe2O4 shell, and oleate capping ligands, with an overall diameter of 12.5 nm. We performed in situ small- and wide-angle X-ray scattering experiments during the entire period of solvent evaporation and colloidal crystallization. We observed a slow increase in the volume fraction of nanocrystals inside the oil droplets up to 20%, at wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 34 publications
(70 reference statements)
1
67
0
Order By: Relevance
“…properties that differ from those of disordered aggregates, isolated nanocrystals and the bulk phase. [ 4–12 ] The measured speed of sound and its temperature dependence [ 13,14 ] suggest lower supracrystal elastic modulus [ 15 ] in comparison to atomic crystals. Thus, these intrinsic and collective properties of supracrystals offer many potential applications where mechanical properties can play an important role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…properties that differ from those of disordered aggregates, isolated nanocrystals and the bulk phase. [ 4–12 ] The measured speed of sound and its temperature dependence [ 13,14 ] suggest lower supracrystal elastic modulus [ 15 ] in comparison to atomic crystals. Thus, these intrinsic and collective properties of supracrystals offer many potential applications where mechanical properties can play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that solid microspheres in oil‐water emulsions can be produced under the influence of weak nanoparticle confinement at the fluid interface combined with control of thermal fluctuations. [ 7,23,24 ] The thermal fluctuations at the fluid interface need to be reduced in order to produce hollow assemblies of nanomaterials. This can be achieved via tuning surface properties using various ligand modifications such as chemical cross‐linking, specific ligand interactions or other nanoparticle stabilizers at the fluid interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, stronger attractions of 2 kT already decreased the volume fraction to 0.11 and caused the systems to fall out of equilibrium. [26,27] We are interested in using the high refractive indexes of TiO 2 NRs for optical applications, for which it is advantageous if they can be used over as broad range of volume fractions as possible. This can be achieved if the (hard) particle shape dominates the phase behavior, while particle charges and interparticle attractions can be neglected.…”
mentioning
confidence: 99%
“…The thermal decomposition of copper-dodecanethiolates usually leads to spheroidal Cu 2−x S nanocrystals, but chloride stabilization of the stacks of lamellar copper-thiolate supramolecular complexes led to 2D-constrained stack-templated nucleation and growth, in which growth in the thickness direction is inhibited (allowing only the lateral growth). Another fascinating example is the formation of supraparticles (∼700 nm) from nanocrystals (∼12 nm) confined within oil droplets in an oil-in-water emulsion upon slow evaporation [96]. The nanoparticles consisted of an FeO core, a CoFe 2 O 4 shell, and oleate capping ligands.…”
Section: In Situ Studies Of Nucleation and Growthmentioning
confidence: 99%
“…Upon evaporation, the volume fraction of particles inside the oil droplets gradually increased up to~20%, at which crystallization occurred instantaneously forming face-centered cubic (fcc) domains. Computer simulations showed that crystallization at such a low volume fraction is only possible if attractive interactions between colloidal nanoparticles are significant [96]. The evaporation induced self-assembly of lead sulfide (PbS) nanoparticles was studied by in situ SAXS [97].…”
Section: In Situ Studies Of Nucleation and Growthmentioning
confidence: 99%